2013
DOI: 10.1186/1471-2458-13-1123
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and determinants of impaired fasting glucose in the population of Taiwan

Abstract: BackgroundA current prevalence and relevant risk factors for impaired fasting glucose (IFG) have been reported by various ethnic groups and countries. By contrast, nationwide data for the incidence of IFG in Taiwan have not been presented in the past 15 years. The aim for this manuscript was to estimate the prevalence of IFG and associated risk factors in the population of Taiwan.MethodsFor this cross-sectional research, we used a nationally representative sample (N = 2604) obtained from the 2005–2008 Nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
6
8
0
Order By: Relevance
“…Another study investigated the determinants of IFG in a population of Taiwan and showed that the likelihood of IFG was increased by 1.03 for each additional year of life, and subjects who were overweight or obese exhibited a higher probability of IFG [ 39 ]. Our study also found that men and 60–69 years old subjects had a significantly higher incidence of IFG [ 38 , 40 , 41 , 42 ]. Additionally, subjects with a higher BMI were more likely to develop IFG and Diabetes compared to subjects with the normal weight.…”
Section: Discussionsupporting
confidence: 73%
“…Another study investigated the determinants of IFG in a population of Taiwan and showed that the likelihood of IFG was increased by 1.03 for each additional year of life, and subjects who were overweight or obese exhibited a higher probability of IFG [ 39 ]. Our study also found that men and 60–69 years old subjects had a significantly higher incidence of IFG [ 38 , 40 , 41 , 42 ]. Additionally, subjects with a higher BMI were more likely to develop IFG and Diabetes compared to subjects with the normal weight.…”
Section: Discussionsupporting
confidence: 73%
“…Our observation of a T2DM prevalence of 1.3 and 0.9% for men and women at baseline was somewhat lower than data among participants from the NHANES studies 2003–2006 (24–33 years of age: 4.4% total diabetes) and 2007–2009 (20–39 years of age: 2.5% total diabetes) [ 8 , 21 ]. In line with cross sectional studies using the current ADA cut point we have found an association between BMI and the prevalence of IFG [ 22 , 23 ]. However there is a lack of longitudinal studies on the risk of incident IFG.…”
Section: Discussionsupporting
confidence: 88%
“… 2 , 4 This reduction was made because patients with a fasting blood glucose level of between 5.6 and 6.1 mmol/L exhibit a higher prevalence of DM compared to people with a fasting blood glucose level lower than 5.6 mmol/L. 11 This leads to confusion because both of the criteria are used for diagnosis in different stroke trials.…”
Section: Impaired Fasting Plasma Glucosementioning
confidence: 99%